(untitled) (IMC Journal of Medical Science, 2020)
Background: Accurate and early diagnosis of enteric fever is a diagnostic challenge where facility for blood culture is not available. As a result, Widal test is still used widely in resource limited settings. Recently, user-friendly rapid immunochromatographic tests (ICT) have been introduced for quick diagnosis of enteric fever. So, we evaluated sensitivity and specificity of an immunochromatography based Salmonella Typhi IgM/IgG test kit and Widal test compared to blood culture for the diagnosis of enteric fever. Method: The study was conducted in the Department of Microbiology, Ibrahim Medical College (IMC) and Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) from June 2017 to September 2017. Clinically suspected enteric fever cases were included. Blood culture, Widal and Salmonella Typhi IgM/IgG detecting ICT were employed for the diagnosis of enteric fever. Results: Out of 71 suspected cases of enteric fever, blood culture was positive in 36 cases (50.7%) while 42 (59.15%) and 35 (49.29%) cases were positive by Widal test and ICT respectively. Widal and ICT had sensitivity and specificity of 100% and 89.9% and 82.9% & 91.4% respectively. Conclusion: Findings of the study suggest that both Widal and immunochromatographic tests can be used interchangeably for rapid diagnosis of enteric fever. Ibrahim Med. Coll. J. 2020; 14(1): 18-25